Food systems for healthier diets in Nigeria: A research agenda - Maziya-Dixon, Busie; Achterbosch, Thom; Adelekan, Delana; Adeyemi, Olutayo; Ajieroh, Victor; Akerele, Dare; Akinola, Adebayo A.; Alamu, Emmanuel Oladeji; van Berkum, Siemen; Byrd, Kendra A.; Nijhuis, Aafke; Ojide, Makuachukwu; et al. (International Food Policy Research Institute, 2021)
Malnutrition, mostly resulting from poor food, health, and care practices, is related to physiological, socioeconomic, and psychological factors and remains one of the leading causes of mortality in children under five years of age in low- and middle-income countries. Nigeria, as with many parts of the world, is experiencing a multiple malnutrition burden, where undernutrition, including micronutrient deficiencies, exists alongside overweight, obesity, and associated diet-related non-communicable diseases. Recent data show that 37 percent of children under five years of age are stunted while 68 percent suffer some degree of anaemia. Overweight and obesity are also common among adults with prevalence rate of about 33 percent. The Nigerian government embraces sustainable food system approaches in its policy and programmes to address malnutrition problems in the country. Food systems approaches take a holistic understanding of all activities and processes involved in food production, processing, storage, transportation, trade, transformation, retail, and consumption.